1. Analisis Pertumbuhan; Kelulushidupan dan Produksi Biomass Larva Udang Vannamei dengan Pemberian Pakan Artemia sp. Produk Lokal yang Diperkaya Chaetoceros calcitrans dan Skeletonema coctatum - Vivi Endar Herawati; Johannes Hutabarat (Fakultas Perikanan Universitas Pekalongan, 2016)
Natural food is the best food for fish because the nutrient cannot be replaced by artificial food. Artemia is one of the best available live food for larvae shrimp (L. vannamei), it is due to Artemia has a good nutrient for larvae shrimp. The purpose of the study is to the influence of the growth, survival and biomass weight through feeding larval shrimp Artemia sp. local products fortified). Tested animals that used were larvae of shrimp with average stages PL1-PL10, this study was conducted by using completely randomized experimental design with 4 treatments and 3 replicates. The results showed that there were significant effects (P<0.05) on biomass of shrimp larvae fed by Artemia sp. local products enriched by diatom, which the Artemia sp. local products fed by C.calcitrans and S.costatum is the best treatment with 5.84±0.6%; for biomass and showed that there were significant effect (P<0.05) on biomassof shrimp larvae fed by Artemia sp. local products enriched by diatom is 5,93±0,12 gr and 87,62 ± 2,52%. For highest survival rate showed that there were significant effects (P<0.05) on biomass of shrimp larvae fed by Artemia sp. local products enriched by diatom with the highest biomass of shrimp larvae fed by Artemia sp. Local products fed by C.calcitrans and S.costatumKeywords : Local Artemia sp.; Growth; Survival rate; Biomass; Vannamei larvae; Diatom